Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So $h(t)=t^{\frac{3}{4}}-7t^{\frac{1}{4}}$. So I need to set $h'(t)=0$. So for $h'(t)$ the fattest I've gotten to simplifying os $h'(t)=\frac{3}{4 \sqrt[4]{t}}-\frac{7}{4\sqrt[4]{t^3}}$ and that is as farthest as I can simplify. So i'm having a had time having $h'=0$ So could someone show me how to properly simplify and find the critical values step by step I would immensely appreciate it. In the most recent material we have covered in class ir seems that my biggest struggle comes from simplifying completely. Thanks in advance for the help.

share|cite|improve this question
Pull out a factor of $\frac{1}{4\sqrt[4]{t^3}}$. You know that isn't $0$, so the other factor must be $0$. The other factor looks simpler. – Daniel Fischer Jul 12 '14 at 23:36
up vote 5 down vote accepted

$$h'(t)=\frac{3}{4 t^{\frac{1}{4}}}-\frac{7}{4t^{\frac{3}{4}}}=\frac{3t^{\frac{2}{4}}-7}{4t^{\frac{3}{4}}}=\frac{3t^{\frac{1}{2}}-7}{4t^{\frac{3}{4}}}$$

$$h'(t)=0 \Rightarrow 3t^{\frac{1}{2}}-7=0 \Rightarrow t^{\frac{1}{2}}=\frac{7}{3} \Rightarrow t=\frac{49}{9}$$

share|cite|improve this answer
Thanks a lot, but I am having trouble understanding how you went from $\frac{3}{4 t^{\frac{1}{4}}}-\frac{7}{4t^{\frac{3}{4}}}->\frac{3t^{\frac{2}{4}}-7} {4t^{\frac{3}{4}}}$ If you could explain I'd really appreciate it. Thanks in advance. – Kenshin Jul 12 '14 at 23:58
@Kenshin Multiply the first fraction by $\frac{t^\frac{1}{2}}{t^{\frac{1}{2}}}$. Now in that denominator $4t^{\frac{1}{4}}t^\frac{1}{2}=4t^{\frac{3}{4}}$, and you can join the two fractions as one. – J. W. Perry Jul 13 '14 at 0:01
Thanks a lot @J.W.Perry! Appreciate the help. – Kenshin Jul 13 '14 at 0:20


$\Rightarrow$ $0=h'(t)=\frac{3}{4}t^{-\frac{1}{4}}-\frac{7}{4}t^{-\frac{3}{4}}=\frac{3}{4}t^{-\frac{3}{4}+\frac{2}{4}}-\frac{7}{4}t^{-\frac{3}{4}}=\frac{3}{4}t^{-\frac{3}{4}}t^{\frac{2}{4}}-\frac{7}{4}t^{-\frac{3}{4}}=t^{-\frac{3}{4}}(\frac{3}{4}t^{\frac{2}{4}}-\frac{7}{4})$

Thus $t=(\frac{7}{3})^2$ Since one factor have to be $0$ and $t^{-\frac{3}{4}}$ is impossible.

share|cite|improve this answer


To make your life easier, just define $x=t^{\frac{1}{4}}$. So $h(t)=x^3-7x$ and then $$\frac{dh}{dt}=\frac{dh}{dx}\frac{dx}{dt}=(3x^2-7)\frac{dx}{dt}$$ So,$h'(t)=0$ if $x^2=\frac{7}{3}$ that is to say $\sqrt t=\frac{7}{3}$ then $t=\frac{49}{9}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.